The South American wolf spider genus Birabenia Mello-Leitão, 1941 (Araneae: Lycosidae: Lycosinae) - Piacentini, Luis Norberto (2013)
The wolf spider genus Birabenia Mello-Leitão, 1941 is revalidated, comprising B. birabenae Mello-Leitão (type species) and B. vittata (Mello-Leitão) comb. n. The monotypic genus Melloicosa Roewer is synonymised with Birabenia by the transfer of its type species Gnatholycosa vittata Mello-Leitão. Three species, Hogna taeniata (Mello-Leitão), Geolycosa sanogastensis (Mello-Leitão) and Paratrochosina murina (Mello-Leitão) are considered junior synonyms of B. birabenae. Representatives of Birabenia show affinities with Trochosa C. L. Koch but can be distinguished by the presence of one pair of apical spines or none on the ventral side of tibia I of females, the presence of four teeth on the cheliceral retromargin, a shorter furrow on the prolateral side of the tegulum on the male bulb and by having more than seven macrosetae at the tip of cymbium. Birabenia is distributed from north-western Argentina to southern Uruguay.